2018
DOI: 10.1126/science.aas9411
|View full text |Cite
|
Sign up to set email alerts
|

Ancient goat genomes reveal mosaic domestication in the Fertile Crescent

Abstract: Current genetic data are equivocal as to whether goat domestication occurred multiple times or was a singular process. We generated genomic data from 83 ancient goats (51 with genome-wide coverage) from Paleolithic to Medieval contexts throughout the Near East. Our findings demonstrate that multiple divergent ancient wild goat sources were domesticated in a dispersed process that resulted in genetically and geographically distinct Neolithic goat populations, echoing contemporaneous human divergence across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
157
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(190 citation statements)
references
References 120 publications
11
157
0
3
Order By: Relevance
“…() proposed that this weak phylogeographic structure likely resulted from frequent transportation for commercial trade or migratory and exploratory movements by humans. This weak phylogeographic structure was also supported by the domestication of multiple divergent wild goats (Daly et al., ).…”
Section: Discussionmentioning
confidence: 87%
“…() proposed that this weak phylogeographic structure likely resulted from frequent transportation for commercial trade or migratory and exploratory movements by humans. This weak phylogeographic structure was also supported by the domestication of multiple divergent wild goats (Daly et al., ).…”
Section: Discussionmentioning
confidence: 87%
“…S3 to S6, and table S3 ), including the earliest known Chinese archaeological samples in Neolithic age ( 14 ). Together with the publicly available genomic sequences for modern goat and bezoar ( 5, 15 ), as well as ancient genomes ( 6 ) ( table S4 ), we compiled a worldwide collection of 164 modern domestic goats, 52 ancient goats, 24 modern bezoars and four ancient bezoars.…”
Section: Resultsmentioning
confidence: 99%
“…The goat ( Capra hircus ) was one of the first domesticated livestock species, demonstrating remarkable adaptability and versatility ( 2, 3 ), and has been intimately associated with human dispersal ( 4 ). Recent studies have identified candidate targets of selection during goat domestication, including loci related to pigmentation, xenobiotic metabolism and milk production ( 5, 6 ); however, the evolutionary dynamics of key genes involved in adaptation during the early phase of domestication remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In each of these species, bottlenecks appear to be quite weak early in the domestication process, suggesting that even when single domestication events occurred, populations were not as small as originally thought. These data combine to give an unprecedented time series of material to see how domestication occurred in real time and are providing new insights, suggesting, for example, that the “domestication bottleneck paradigm may not be as universal as once thought.” This has been shown most recently in goats, where a “mosaic” of events appears to be the most likely scenario in goat domestication (Daly et al., ).…”
mentioning
confidence: 81%
“…These data combine to give an unprecedented time series of material to see how domestication occurred in real time and are providing new insights, suggesting, for example, that the "domestication bottleneck paradigm may not be as universal as once thought." This has been shown most recently in goats, where a "mosaic" of events appears to be the most likely scenario in goat domestication (Daly et al, 2018).…”
mentioning
confidence: 84%